2017
DOI: 10.1038/bjc.2016.451
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA 0000096 affects cell growth and migration in gastric cancer

Abstract: Background:Circular RNAs (circRNAs) are a class of non-coding RNAs broadly expressed in cells of various species. Their role in cancers, especially in gastric cancer, is poorly understood.Methods:Circular RNA 0000096 (hsa_circ_0000096) levels in 101 paired gastric cancer tissues and adjacent non-tumorous tissues from patients with gastric cancer were detected by real-time quantitative reverse transcription-polymerase chain reaction. A receiver operating characteristic curve was generated to evaluate the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
177
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 30 publications
1
177
0
Order By: Relevance
“…Previous studies have reported that circRNAs play a crucial role in cancer biological processes, such as proliferation, migration, and metastasis . Our study revealed that the decreased hsa_circ_0000567 was negatively correlated with tumor size, lymph metastasis, distal metastasis, and TNM stage in patients with CRC (Table ).…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have reported that circRNAs play a crucial role in cancer biological processes, such as proliferation, migration, and metastasis . Our study revealed that the decreased hsa_circ_0000567 was negatively correlated with tumor size, lymph metastasis, distal metastasis, and TNM stage in patients with CRC (Table ).…”
Section: Discussionsupporting
confidence: 50%
“…These mean that circRNAs are not easy to be degraded. About their functions, circRNAs are regarded as microRNA (miRNA) sponges and transcriptional regulators . Recently, many researches have proved that circRNAs can be potential novel biomarkers in diagnosing cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that circRNAs play important regulatory roles in gene expression and may account for initiation and development of cancers or noncancerous diseases . According to previous researches, circular RNA ciRS‐7 (Cdr1as), hsa_circ_0001649 and hsa_circ_0005075, are differently expressed between HCC tissues and adjacent normal tissues …”
Section: Discussionmentioning
confidence: 99%
“…As regulatory noncoding RNAs, microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been studied for several years. Nowadays, circular RNAs (circRNAs), a new type of regulatory noncoding RNAs, are becoming the highlight RNA molecules . CircRNAs are a class of endogenous RNAs with a stable structure formed by special loop splicing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation